Digital Technologies in the Economy - Anvarovich, Nozimov Eldor (International Journal on Orange Technologies, 2023)
Currently, digital technologies have penetrated into all spheres of public life, including the economy. The process of digitalization is becoming increasingly important and under its influence, new technologies are being applied and introduced into the economy. The use of new technologies in this area can help companies achieve greater growth and solve many problems and tasks more efficiently. Large amounts of data, as well as various digital gadgets, have already ceased to be something amazing, and have become widely used in all spheres of human activity. This work contains a number of definitions that reveal the essence of the term "digitalization". In this article I will look at some of the technologies that are currently being used and are of the greatest importance in the economy, as well as business.